Study on inflammation and fibrogenesis in MAFLD from 2000 to 2022: a bibliometric analysis - Luo, Kuanhong; Chen, Yang; Fang, Shuzheng; Wang, Siqi; Wu, Zhixin; Li, Huiqing (Frontiers in Endocrinology, 2023)
Chronic inflammation and fibrosis are significant factors in the pathogenesis of metabolic-associated fatty liver disease (MAFLD). In this study, we conducted a bibliometric analysis of publications on inflammation and fibrogenesis in MAFLD, with a focus on reporting publication trends. Our findings indicate that the United States and China are the most productive countries in the field, with the University of California San Diego being the most productive institution. Over the past 23 years, Pro. Diehl AM has published 25 articles that significantly contributed to the research community. Notably, the research focus of the field has shifted from morbid obesity and adiponectin to metabolic syndrome, genetics, and microbiome. Our study provides a comprehensive and objective summary of the historical characteristics of research on inflammation and fibrogenesis in MAFLD, which will be of interest to scientific researchers in this field. institutions are shown in Table 1. Interestingly, among the top ten productive institutions, seven were from the USA, two came from China, and one from Italy. The University of California San Diego published the most articles (74 articles), followed by Duke University (n = 43), Shanghai Jiao Tong University (n = 41), Mayo University (n = 37), and Harvard Medical School (n =35).Over the past 23 years, 606 scholarly journals have published a total number of 2348 original articles. We used VOSviewer to show journal influence. the top 10 most cited journals related to the topic of inflammation and fibrogenesis in MAFLD are presented in Table 2. According to the analysis, hepatology publications had the most publications (141 papers) and the most citations (22934) during the past 23 years, followed by those in Gastroenterology (9737), Journal of Hepatology (6191), Plos One (3941), and New England Journal of Medicine (3421). In addition, eight journals were in the Q1 Journal Citation Reports (JCR) division, indicating their high academic standing. Notably, seven of these journals are from the USA, and the remaining three are from the Netherlands and the UK, with all of them being developed countries and therefore providing an important platform for the research development in this field.